PEMBINAAN KERUKUNAN UMAT BERAGAMA DI DAERAH TRANSMIGRASI PALINGKAU ASRI - Marmiati Mawardi (Analisa: Journal of Social Science and Religion, 2008)
Harmony management of religious community at transmigration areaof Palingkau Asri, in particular is not exist, is carried out by Islamicand Christian leaders. It is packed in religious speeches. This management is run by the government at the beginning of transmigration forthe last three year, i.e. during 1997-2000. Afterward, religious leadersmanage Islamic community independently. And GKE Palingkau manages Christian community.